Pajak Penghasillan Pasal 26 - Dini Vientiany; Nur Ajizah Harahap; Sony Raudha; M Fikri Ariga (Kajian Ekonomi dan Akuntansi Terapan, 2025)
Article 26 Income Tax (PPh Article 26) is a tax imposed on income received by foreign taxpayers from sources within Indonesia. This tax applies to foreign entities or individuals who do not reside, are not domiciled, and do not have a permanent establishment in Indonesia. Types of taxable income include interest, dividends, royalties, rent, and service fees. The standard tax rate is 20% of the gross income, but it can be reduced if a Double Tax Avoidance Agreement (DTAA) exists between Indonesia and the taxpayer’s country. The Indonesian income payer is responsible for withholding the tax. After withholding, the tax must be paid to the government by the 10th of the following month and reported to the tax authority by the 20th. To apply DTAA rates, the foreign taxpayer must submit a Certificate of Domicile (CoD). This mechanism ensures that Indonesia maintains its right to tax income derived within its territory. By understanding the procedures for withholding, paying, and reporting Article 26 tax, taxpayers can fulfill their tax obligations correctly and avoid administrative penalties.